(untitled) (Fiep Bulletin - online, 2013)
The process of aging is inherent in every human being characterized by changes arising from the very process of life. One of the concerns of the National Health Policy on Elderly is the promotion of a full and quality service. As public health policy, embracement is an attempt to promote an important link between the health team and user. The study aims to characterize embracement as a strategy to reorganize the work process in the Family Health Units (FHUs). This is an exploratory study conducted among the units of Family Health in the town of João Pessoa, Paraiba, Brazil. For data collection, a survey was held among the services beyond the assystematic observation. The collected data were prepared in the form of a table and later analyzed, in a reflexive way. It appeared that embracement is in the process of implementation and development, with a few units using the strategy of reception. It was found that in most searched units the care to the elderly is not seen so differently at home, as stipulated by the Statute of the Elderly, so that it is necessary its fulfillment.